แนวทางการจัดทำระบบเวชระเบียนสัตว์ป่วยสำหรับรักษาสัตว์ป่วยในพื้นที่นครปฐม - แสงเทียน อยู่เถา (2018)
The veterinary medical record (VMR) study is aimed to explore the preparation of guideline that develops VMR model for veterinary cares in Nakhonpathom area. The study methodology included between expert interview, focus group discussion, and observation. Total ten experts and ten related key-informants were interviewed. One focus group discussion was set up with 20 participants. Two veterinary hospitals, two pet clinics, and 2 livestock offices were observed. The study found that type of animal patients is classified into small pet, wildlife, large animal, and special or alien animal. In some places, horse and aquatic animals are separated from this classification. According to VMR system, animal are divides into new animal patient, old animal patient, and admitted animal patient (in-patient). The detail of pet owner is also recorded with in the system. The VMR is recorded by HN in the veterinary hospital and by address in the pet clinics. Moreover, the study found that the VMR system of each veterinary care is not unique. VMR system is not standardized due to lack of personnel such as VMR recorder (Medical Record Officer), veterinary nurse, public relation officer, and hospital ship as well as the VMR standard guideline from Veterinarian Council. In addition, the VMR is not indicated in the veterinary hospital accreditation and the information system is not included in the university veterinary studying program. The current medical recording program is not covered all needed records in the veterinary hospitals. Therefore, it is needed to develop VMR processes such as identification, operation, laboratory relation, personnel, the connection with veterinary council, VMR duplication, VMR standard, training, and information system for each type of veterinary cares such as veterinary hospital, pet clinics, and livestock agency. This study suggests that the veterinary cares in Nakhonpathom area should bring the international VMR system or the worldwide accepted VMR guideline to record the animal information. However, the VMR system must be applied in consistent with type and size of each veterinary cares. The recommendation for future study includes the development of VMR pattern, specialist personnel, medical record standard, and program for animal patient information system in terms of operation and standard.